Fluorine-containing copolymer
Patent Information
- Application Number
- CN202280015022.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-26
- Filing Date
- 2022-02-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-02-28
AI Technical Summary
[0019] According to the present invention, a fluorinated copolymer can be provided, which can be molded at a high injection speed by injection molding to obtain a beautiful injection molded body, and can form a thin coating layer on a small diameter core wire at a high speed by extrusion molding, and can obtain a molded body with excellent wear resistance at 80°C, solvent crack resistance, rigidity at 100°C, tensile creep resistance at 100°C, and durability under repeated loads.
Smart Images

Figure BDA0004394347880000071 
Figure BDA0004394347880000181 
Figure BDA0004394347880000231
Abstract
Description
Technical Field
[0001] This invention relates to fluorinated copolymers. Background Technology
[0002] Patent Document 1 describes a tetrafluoroethylene / hexafluoropropylene copolymer comprising a copolymer obtained by copolymerizing at least tetrafluoroethylene and hexafluoropropylene, without mixing it with a resin whose melting point differs from that of the copolymer by more than 20°C. In a melt viscoelasticity test under conditions of an atmosphere temperature of 310°C and an angular frequency of 0.01 rad / s, the complex viscosity is 2.0 × 10⁻¹⁰. 3 Pa·s ~ 10.0 × 10 3 Pa·s, with a storage modulus of 0.1 Pa to 3.5 Pa.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: International Publication No. 2009 / 102660 Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] The purpose of this invention is to provide a fluorinated copolymer that can be molded at high injection speed to obtain a beautiful injection molded body, and can form a thin coating layer on a small diameter core wire at high speed through extrusion molding, and can obtain a molded body with excellent wear resistance at 80°C, solvent crack resistance, rigidity at 100°C, tensile creep resistance at 100°C, and durability under repeated loads.
[0008] Methods for solving problems
[0009] According to the present invention, a fluorinated copolymer is provided, which is a fluorinated copolymer containing tetrafluoroethylene units, hexafluoropropylene units and perfluoro(propyl vinyl ether) units, wherein the content of hexafluoropropylene units is 10.3% to 12.2% by mass relative to all monomer units, the content of perfluoro(propyl vinyl ether) units is 1.2% to 1.6% by mass relative to all monomer units, and the melt flow rate at 372°C is 13.0 g / 10 min to 17.0 g / 10 min.
[0010] The content of hexafluoropropylene units is preferably 10.7% to 11.5% by mass relative to all monomer units.
[0011] The content of perfluoro(propyl vinyl ether) units is preferably 1.2% to 1.5% by mass relative to all monomer units.
[0012] The melt flow rate at 372℃ is preferably 14.1 g / 10 min to 16.0 g / 10 min.
[0013] The amount of -CF2H relative to every 10 6 Each main chain has more than 50 carbon atoms.
[0014] The total number of carbonyl-containing terminal groups, -CF=CF2, and -CH2OH relative to 10 6 The number of carbon atoms in the main chain is preferably less than 100.
[0015] In addition, according to the present invention, an injection-molded article is provided which contains the above-mentioned fluorinated copolymer.
[0016] In addition, according to the present invention, a coated wire is provided having a coating layer containing the above-mentioned fluorinated copolymer.
[0017] In addition, according to the present invention, a molded body is provided, which is a molded body containing the above-mentioned fluorinated copolymer, wherein the molded body is a bolt, filter cover, tube, membrane or wire cover.
[0018] The effects of the invention
[0019] According to the present invention, a fluorinated copolymer can be provided, which can be molded at a high injection speed by injection molding to obtain a beautiful injection molded body, and can form a thin coating layer on a small diameter core wire at a high speed by extrusion molding, and can obtain a molded body with excellent wear resistance at 80°C, solvent crack resistance, rigidity at 100°C, tensile creep resistance at 100°C, and durability under repeated loads. Detailed Implementation
[0020] The specific embodiments of the present invention will be described in detail below, but the present invention is not limited to the following embodiments.
[0021] The fluorinated copolymer of the present invention contains tetrafluoroethylene (TFE) units, hexafluoropropylene (HFP) units, and perfluoro(propyl vinyl ether) (PPVE) units.
[0022] Patent document 1 discloses a TFE / HFP copolymer (FEP) that improves formability in melt extrusion molding, particularly significantly reducing molding defects during high-speed molding in wire extrusion coating molding, and producing wires with low transmission loss (attenuation). While such FEP can form good wire coatings, it cannot be said that it is necessarily suitable for applications other than wire coating.
[0023] Fluoropolymers such as TFE / HFP copolymers (FEP) exhibit excellent chemical resistance, making them suitable for use as forming materials for bolts in environments involving contact with chemicals. They are also used as filter housings for filtering chemicals. These molded bodies have areas prone to wear due to tightening or loosening, requiring abrasion resistance and resistance to cracking even after contact with chemicals. Furthermore, they must not deform under stress or deteriorate under repeated loading. Therefore, there is a need for fluorinated copolymers that provide high-temperature rigidity, excellent tensile creep resistance at 100°C, excellent durability under repeated loading, and excellent high-temperature abrasion resistance and solvent cracking resistance.
[0024] Discovery: By adjusting the content of HFP and PPVE units in fluorinated copolymers containing TFE, HFP, and PPVE units, as well as the melt flow rate, to extremely limited ranges, the abrasion resistance at 80°C, solvent crack resistance, rigidity at 100°C, tensile creep resistance at 100°C, and durability under repeated loads of the molded articles obtained from the fluorinated copolymers are significantly improved. Furthermore, by using injection molding to mold the fluorinated copolymers of the present invention at high injection speeds, beautiful injection-molded articles can be obtained.
[0025] Furthermore, by using extrusion molding to form the fluorinated copolymer of the present invention, a thin coating layer can be formed at high speed on a core wire with a small diameter, and a film of uniform thickness can be formed at a high molding speed. Thus, the fluorinated copolymer of the present invention can be used not only as a material for bolts and filter covers, but also for a wide range of applications such as coating pipes, membranes, or wires.
[0026] The fluorinated copolymer of the present invention is a melt-processable fluoropolymer. Melt processability refers to the ability to melt and process the polymer using existing processing equipment such as extruders and injection molding machines.
[0027] The content of HFP units in the fluorinated copolymer is 10.3% to 12.2% by mass relative to all monomer units, preferably 10.4% by mass or more, more preferably 10.5% by mass or more, even more preferably 10.6% by mass or more, particularly preferably 10.7% by mass or more, preferably 12.0% by mass or less, more preferably 11.8% by mass or less, even more preferably 11.7% by mass or less, even more preferably 11.6% by mass or less, especially more preferably 11.5% by mass or less, particularly preferably 11.3% by mass or less, and most preferably 11.1% by mass or less. If the content of HFP units is too low, it is impossible to obtain a molded article with excellent abrasion resistance and solvent cracking resistance at 80°C. If the content of HFP units is too high, it is impossible to obtain a molded article with excellent rigidity at 100°C, tensile creep resistance at 100°C, and durability under repeated loads.
[0028] The content of PPVE units in the fluorinated copolymer is 1.2% to 1.6% by mass relative to all monomer units, preferably less than 1.5% by mass. If the content of PPVE units is too low, it is impossible to obtain a molded article with excellent abrasion resistance and solvent cracking resistance at 80°C. If the content of PPVE units is too high, it is impossible to obtain a molded article with excellent rigidity and tensile creep resistance at 100°C.
[0029] The content of TFE units in the fluorinated copolymer is preferably 86.2% by mass or more, more preferably 86.3% by mass or more, further preferably 86.6% by mass or more, even more preferably 86.8% by mass or more, particularly preferably 87.0% by mass or more, most preferably 87.4% by mass or more, preferably 88.5% by mass or less, more preferably 88.4% by mass or less, further preferably 88.3% by mass or less, even more preferably 88.2% by mass or less, and particularly preferably 88.1% by mass or less. Alternatively, the content of TFE units can be selected such that the total content of HFP units, PPVE units, TFE units, and other monomer units is 100% by mass.
[0030] The fluorinated copolymer of the present invention only needs to contain the above three monomer units. It can be a copolymer containing only the above three monomer units, or it can be a copolymer containing the above three monomer units and other monomer units.
[0031] As for other monomers, there are no particular limitations as long as they can copolymerize with TFE, HFP, and PPVE. They can be either fluorinated or non-fluorinated monomers.
[0032] As a fluorinated monomer, it is preferably selected from trifluorochloroethylene, vinylidene fluoride, vinylidene fluoride, trifluoroethylene, hexafluoroisobutylene, CH2=CZ. 1 (CF2) n Z 2 (where Z) 1 For H or F, Z 2 The monomer shown is represented by H, F, or Cl, where n is an integer from 1 to 10, CF2 = CF - ORf 1 (where Rf) 1 Perfluoro(alkyl vinyl ether) [PAVE] (except for PPVE) represented by perfluoroalkyl groups having 1 to 8 carbon atoms, CF2=CF-O-CH2-Rf 2 (where Rf) 2It is at least one of the following groups: alkyl perfluorovinyl ether derivatives (represented by a perfluoroalkyl group having 1 to 5 carbon atoms), perfluoro-2,2-dimethyl-1,3-dioxacyclopentene [PDD], and perfluoro-2-methylene-4-methyl-1,3-dioxacyclopentane [PMD].
[0033] As CH2=CZ 1 (CF2) n Z 2 Examples of the monomers shown include CH2=CFCF3, CH2=CH-C4F9, and CH2=CH-C6F. 13 CH2=CF-C3F6H, etc.
[0034] As CF2 = CF - ORf 1 Examples of perfluorinated (alkyl vinyl ethers) include CF2=CF-OCF3 and CF2=CF-OCF2CF3.
[0035] Examples of non-fluorinated monomers include hydrocarbon monomers capable of copolymerizing with TFE, HFP, and PPVE. Examples of hydrocarbon monomers include: olefins such as ethylene, propylene, butene, and isobutylene; alkyl vinyl ethers such as ethyl vinyl ether, propyl vinyl ether, butyl vinyl ether, isobutyl vinyl ether, and cyclohexyl vinyl ether; vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl valerate, vinyl pentanoate, vinyl hexanoate, vinyl octanoate, vinyl decanoate, vinyl tert-carbonate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl benzoate, p-tert-butylbenzoate, vinyl cyclohexanecarboxylate, and vinyl monochloroacetate. Vinyl esters such as vinyl adipate, vinyl acrylate, vinyl methacrylate, vinyl crotonate, vinyl sorbate, vinyl cinnamate, vinyl undecenoate, vinyl glycolate, vinyl hydroxypropionate, vinyl hydroxybutyrate, vinyl hydroxyvalerate, vinyl hydroxyisobutyrate, and vinyl hydroxycyclohexanecarboxylate; alkyl allyl ethers such as ethyl allyl ether, propyl allyl ether, butyl allyl ether, isobutyl allyl ether, and cyclohexyl allyl ether; and alkyl allyl esters such as ethyl allyl ester, propyl allyl ester, butyl allyl ester, isobutyl allyl ester, and cyclohexyl allyl ester.
[0036] As non-fluorinated monomers, they can also be hydrocarbon monomers containing functional groups capable of copolymerizing with TFE, HFP, and PPVE. Examples of hydrocarbon monomers containing functional groups include hydroxyalkyl vinyl ethers such as hydroxyethyl vinyl ether, hydroxypropyl vinyl ether, hydroxybutyl vinyl ether, hydroxyisobutyl vinyl ether, and hydroxycyclohexyl vinyl ether; non-fluorinated monomers with glycidyl groups such as glycidyl vinyl ether and glycidyl allyl ether; non-fluorinated monomers with amino groups such as aminoalkyl vinyl ether and aminoalkyl allyl ether; non-fluorinated monomers with amide groups such as (meth)acrylamide and hydroxymethylacrylamide; bromine-containing alkenes, iodine-containing alkenes, bromine-containing vinyl ethers, and iodine-containing vinyl ethers; and non-fluorinated monomers with nitrile groups.
[0037] The content of other monomer units in the fluorinated copolymer of the present invention is preferably 0 to 2.3% by mass relative to all monomer units, more preferably 1.0% by mass or less, even more preferably 0.5% by mass or less, and particularly preferably 0.1% by mass or less.
[0038] The melt flow rate (MFR) of the fluorinated copolymer is 13.0 g / 10 min to 17.0 g / 10 min, preferably 13.1 g / 10 min or more, more preferably 13.5 g / 10 min or more, further preferably 14.0 g / 10 min or more, particularly preferably 14.1 g / 10 min or more, preferably 16.9 g / 10 min or less, more preferably 16.5 g / 10 min or less, and further preferably 16.0 g / 10 min or less. If the MFR is too low, it is impossible to obtain a molded article with excellent rigidity at 100°C. In addition, if the MFR is too low, it is impossible to obtain a beautiful injection molded article by injection molding at a high injection speed, and it is impossible to form a thin coating layer on a small diameter core wire at a high speed by extrusion molding. If the MFR is too high, it is impossible to obtain a molded article with excellent abrasion resistance and solvent cracking resistance at 80°C.
[0039] In this invention, the melt flow rate is the value obtained according to ASTM D-1238 using a melt flow index tester G-01 (manufactured by Toyo Seiki Co., Ltd.) as the mass (g / 10 min) of polymer flowing out of a die with an inner diameter of 2 mm and a length of 8 mm every 10 minutes under a load of 5 kg at 372 °C.
[0040] MFR can be adjusted by modifying the type and amount of polymerization initiator and the type and amount of chain transfer agent used in monomer polymerization.
[0041] The fluorinated copolymers of the present invention may or may not have -CF2H. Since the fluorinated copolymers are less prone to molding defects such as foaming during melt molding and have excellent heat resistance, the fluorinated copolymers of the present invention preferably have -CF2H. The amount of -CF2H in the fluorinated copolymer relative to 10 6 The number of carbon atoms in the main chain is preferably 50 or more, more preferably 60 or more, even more preferably more than 90, even more preferably more than 120, even more preferably more than 150, particularly preferably more than 200, and most preferably more than 300. The upper limit for the number of -CF2H atoms is not particularly limited; for example, it can be 800. The number of -CF2H atoms can be adjusted, for example, by appropriately selecting the type of polymerization initiator or chain transfer agent, or by the wet heat treatment or fluorination treatment of the fluorinated copolymer described later.
[0042] The fluorinated copolymers of the present invention may or may not have -COF, -COOH, or -CH2OH. In the fluorinated copolymers of the present invention, the total number of -COF, -COOH, and -CH2OH is relative to every 10 6 The number of carbon atoms in the main chain is preferably 100 or less. The total number of -COF, -COOH, and -CH2OH atoms is preferably 90 or less, 80 or less, 70 or less, 60 or less, and 50 or less, in that order. By keeping the total number of -COF, -COOH, and -CH2OH atoms within the above range, molding defects such as foaming are less likely to occur during melt molding of the fluorinated copolymer, and the fluorinated copolymer exhibits excellent heat resistance. The total number of -COF, -COOH, and -CH2OH atoms can be adjusted, for example, by appropriately selecting the type of polymerization initiator or chain transfer agent, or by the wet heat treatment or fluorination treatment of the fluorinated copolymer described later.
[0043] The fluorinated copolymers of the present invention may or may not have carbonyl-containing terminal groups, -CF=CF2, or -CH2OH. In the fluorinated copolymers of the present invention, the total number of carbonyl-containing terminal groups, -CF=CF2, and -CH2OH is relative to every 10 6 The number of carbon atoms in the main chain is preferably 100 or less. The total number of carbonyl-containing terminal groups, -CF=CF2, and -CH2OH is preferably 90 or less, 80 or less, 70 or less, 60 or less, and 50 or less, in that order. By keeping the total number of carbonyl-containing terminal groups, -CF=CF2, and -CH2OH within the above range, molding defects such as foaming are less likely to occur when the fluorinated copolymer is melt-molded, and the fluorinated copolymer exhibits excellent heat resistance. The total number of carbonyl-containing terminal groups, -CF=CF2, and -CH2OH can be adjusted, for example, by appropriately selecting the type of polymerization initiator or chain transfer agent, or by the wet heat treatment or fluorination treatment of the fluorinated copolymer described later.
[0044] The carbonyl-containing terminal groups are, for example, -COF, -COOH, -COOR (R is alkyl), -CONH2, and -O(C=O)OR (R is alkyl). The type of alkyl group (R) in -COOR and -O(C=O)OR is determined by the polymerization initiator, chain transfer agent, etc. used in the manufacture of fluorinated copolymers, and is, for example, alkyl groups with 1 to 6 carbon atoms such as -CH3.
[0045] The fluorinated copolymers of the present invention may or may not have -O (C=O)OR (R is alkyl). Preferably, the total number of -O (C=O)OR (R is alkyl) in the fluorinated copolymers of the present invention is relative to the total number of -O (C=O)OR (R is alkyl) per 10 6 The number of carbon atoms in the main chain is 100 or less. The total number of -O (C=O)OR (R is alkyl) atoms is preferably 90 or less, 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 20 or less, and 15 or less, and may be less than the limit of quantitation (ND). The total number of -O (C=O)OR (R is alkyl) atoms can be adjusted, for example, by appropriately selecting the type of polymerization initiator or chain transfer agent, or by the wet heat treatment or fluorination treatment of the fluorinated copolymer described later.
[0046] The identification of the types of functional groups and the determination of the number of functional groups mentioned above can be achieved using infrared spectroscopy.
[0047] Regarding the number of functional groups, specifically, it was determined using the following method. First, the above-mentioned fluorinated copolymer was cold-pressed to produce a film with a thickness of 0.25 mm to 0.30 mm. The film was analyzed by Fourier transform infrared spectroscopy to obtain the infrared absorption spectrum of the above-mentioned fluorinated copolymer, and a differential spectrum was obtained compared with the background spectrum of a fully fluorinated copolymer without functional groups. The number of functional groups in the above-mentioned fluorinated copolymer was calculated from the absorption peaks of specific functional groups shown in the differential spectrum according to the following formula (A). 6 The number of functional groups N per carbon atom.
[0048] N = I × K / t (A)
[0049] I: Absorbance
[0050] K: Correction coefficient
[0051] t: Membrane thickness (mm)
[0052] For reference, the absorption frequencies, molar absorptivity, and correction factors for some functional groups are shown in Table 1. Furthermore, the molar absorptivity was determined using FT-IR measurements of low-molecular-weight model compounds.
[0053] [Table 1]
[0054] Table 1
[0055]
[0056] The absorption frequencies of -CH2CF2H, -CH2COF, -CH2COOH, -CH2COOCH3, and -CH2CONH2 are tens of Kaiser (cm) lower than those of -CF2H, -COF, free -COOH, and bonded -COOH, -COOCH3, and -CONH2, respectively, as shown in the table. -1 ).
[0057] For example, the number of functional groups in -COF refers to the number of functional groups originating from the absorption frequency of -CF2COF, which is 1883 cm⁻¹. -1 The number of functional groups derived from the absorption peak at 1840 cm⁻¹ and the absorption frequency originating from -CH₂COF were also analyzed. -1 The total number of functional groups obtained from the absorption peak at the given location.
[0058] Alternatively, the number of -CF2H groups can also be determined using a nuclear magnetic resonance (NMR) apparatus. The measurement temperature is set to (the melting point of the polymer + 20) °C, and 19F-NMR is performed. The result is obtained from the peak integral value of the -CF2H groups.
[0059] Functional groups such as the -CF2H group are functional groups present at the ends of the main chain or side chains of fluorinated copolymers, and functional groups present in the main chain or side chains. These functional groups are introduced into fluorinated copolymers, for example, through chain transfer agents or polymerization initiators used in the manufacture of the copolymers. For example, when an alcohol is used as a chain transfer agent, or when a peroxide having a -CH2OH structure is used as a polymerization initiator, -CH2OH is introduced to the ends of the main chain of the fluorinated copolymer. Alternatively, these functional groups are introduced to the ends of the side chains of the fluorinated copolymer by polymerizing monomers containing these functional groups.
[0060] By subjecting the fluorinated copolymer having such functional groups to wet heat treatment, fluorination treatment, or other treatments, a fluorinated copolymer having the number of functional groups within the aforementioned range can be obtained. The fluorinated copolymer of the present invention is more preferably subjected to wet heat treatment.
[0061] The melting point of the fluorinated copolymer is preferably 220°C to 290°C, more preferably 240°C to 280°C. By keeping the melting point within the above range, it is possible to obtain a beautiful injection molded body by injection molding at a high injection speed, and to form a thin coating layer on a small diameter core wire at a high speed by extrusion molding. This results in a molded body with superior abrasion resistance at 80°C, solvent crack resistance, rigidity at 100°C, and durability under repeated loads.
[0062] In this invention, the melting point can be determined using a differential scanning calorimeter (DSC).
[0063] The fluorinated copolymers of the present invention can be manufactured by any of the polymerization methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization. In these polymerization methods, the conditions such as temperature and pressure, the polymerization initiator, chain transfer agent, solvent, and other additives can be appropriately set according to the desired composition and amount of the fluorinated copolymer.
[0064] Oil-soluble free radical polymerization initiators or water-soluble free radical initiators can be used as polymerization initiators.
[0065] As an oil-soluble free radical polymerization initiator, it can be a known oil-soluble peroxide, and the following substances can be cited as representative examples:
[0066] Dialkyl percarbonate esters, such as di-n-propyl percarbonate, diisopropyl percarbonate, and disec-butyl percarbonate;
[0067] Peroxide esters such as tert-butyl peroxide isobutyrate and tert-butyl perpentyl peroxide;
[0068] Dialkyl peroxides such as di-tert-butyl peroxide;
[0069] Di[fluoro(or fluorochloro)acyl] peroxides; etc.
[0070] Examples of diacyl peroxides include those represented by [(RfCOO)-]2 (where Rf is a perfluoroalkyl, ω-hydroperfluoroalkyl, or fluorochloroalkyl).
[0071] Examples of di[fluoro(or fluorochloro)acyl]peroxides include, for example, di(ω-hydro-dodecanoyl)peroxide, di(ω-hydro-tetradecanoyl)peroxide, di(ω-hydro-hexadecanoyl)peroxide, di(perfluorobutyryl)peroxide, di(perfluoropentanoyl)peroxide, di(perfluorohexanoyl)peroxide, di(perfluoroheptanoyl)peroxide, di(perfluorooctanoyl)peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl)peroxide, di(ω-chloro-decanoyl)peroxide, and di(ω-decanoyl)peroxide. Fluorohexyl peroxide, di(ω-chloro-tetrafluorooctanoyl) peroxide, ω-hydro-dodecanoyl-ω-hydrohexadecanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydro-dodecanoyl-perfluorobutyryl-peroxide, di(dichloropentafluorobutyryl) peroxide, di(trichlorooctafluorohexanoyl) peroxide, di(tetrachloroundecanoyl) peroxide, di(pentachlorotetrafluorodecanoyl) peroxide, di(undecatrifluorotetrafluorodienoyl) peroxide, etc.
[0072] As a water-soluble free radical polymerization initiator, it can be a known water-soluble peroxide, such as ammonium salts, potassium salts, sodium salts of persulfate, perboric acid, perchloric acid, superphosphoric acid, and percarbonate, as well as tert-butyl maleate peroxide and tert-butyl hydroperoxide. It may also contain reducing agents such as sulfites, in amounts ranging from 0.1 to 20 times that of the peroxide.
[0073] If an oil-soluble free radical polymerization initiator is used as the polymerization initiator, the formation of -COF and -COOH can be avoided, and the total number of -COF and -COOH in the fluorinated copolymer can be easily adjusted to the above-mentioned range, which is therefore preferred. Furthermore, if an oil-soluble free radical polymerization initiator is used, it also tends to easily adjust the carbonyl-containing terminal groups and -CH2OH to the above-mentioned range. In particular, it is preferable to manufacture the fluorinated copolymer by suspension polymerization using an oil-soluble free radical polymerization initiator. As an oil-soluble free radical polymerization initiator, at least one is preferably selected from the group consisting of dialkyl percarbonate esters and di[fluoro(or fluorochloro)acyl]peroxides, more preferably at least one is selected from the group consisting of di-n-propyl percarbonate, diisopropyl percarbonate, and di(ω-hydro-dodecylfluoroheptyl)peroxide.
[0074] Examples of chain transfer agents include hydrocarbons such as ethane, isopentane, n-hexane, and cyclohexane; aromatics such as toluene and xylene; ketones such as acetone; acetates such as ethyl acetate and butyl acetate; alcohols such as methanol, ethanol, and 2,2,2-trifluoroethanol; thiols such as methyl mercaptan; halogenated hydrocarbons such as carbon tetrachloride, chloroform, dichloromethane, and chloromethane; and 3-fluorobenzotrifluoride. The amount added varies depending on the chain transfer constant of the compound used, and is typically used in the range of 0.01 to 20 parts by mass relative to 100 parts by mass of solvent.
[0075] For example, when using dialkyl peroxide carbonates, di[fluoro(or fluorochloro)acyl]peroxides, etc., as polymerization initiators, the resulting fluorinated copolymers have excessively high molecular weights, sometimes making it difficult to adjust to the desired melt flow rate. However, chain transfer agents can be used to adjust the molecular weight. Fluorinated copolymers are particularly preferably manufactured by suspension polymerization using chain transfer agents such as alcohols and oil-soluble free radical polymerization initiators.
[0076] Examples of solvents include water and mixtures of water and alcohol. Alternatively, the monomers used in the polymerization of the fluorinated copolymers of this invention can also be used as solvents.
[0077] In suspension polymerization, fluorinated solvents can be used in addition to water. Examples of fluorinated solvents include hydrochlorofluorocarbons such as CH3CClF2, CH3CCl2F, CF3CF2CCl2H, and CF2ClCF2CFHCl; chlorofluorocarbons such as CF2ClCFClCF2CF3 and CF3CFClCFClCF3; and perfluoroalkyl hydrocarbons such as perfluorocyclobutane, CF3CF2CF2CF3, CF3CF2CF2CF2CF3, and CF3CF2CF2CF2CF2CF3, with perfluoroalkyl hydrocarbons being preferred. From the perspectives of suspension performance and economy, the amount of fluorinated solvent used is preferably 10 to 100 parts by mass relative to 100 parts by mass of the solvent.
[0078] There is no particular limitation on the polymerization temperature, which can be 0 to 100°C. However, if the decomposition rate of the polymerization initiator is too fast, such as when using dialkyl peroxide carbonate, di[fluoro(or fluorochloro)acyl]peroxide, etc., as the polymerization initiator, it is preferable to use a lower polymerization temperature, such as a polymerization temperature range of 0°C to 35°C.
[0079] The polymerization pressure is appropriately determined based on the type and amount of solvent used, vapor pressure, polymerization temperature, and other polymerization conditions, and is typically 0–9.8 MPaG. The polymerization pressure is preferably 0.1 MPaG–5 MPaG, more preferably 0.5 MPaG–2 MPaG, and even more preferably 0.5 MPaG–1.5 MPaG. Furthermore, a polymerization pressure of 1.5 MPaG or higher can improve production efficiency.
[0080] Examples of additives used in polymerization include suspension stabilizers. There are no particular limitations on existing, well-known suspension stabilizers; methylcellulose, polyvinyl alcohol, etc., can be used. When a suspension stabilizer is used, the suspended particles generated by the polymerization reaction are stably dispersed in the aqueous medium. Therefore, even when using a SUS-made reaction tank without anti-adhesion treatment such as a glass liner, the suspended particles are less likely to adhere to the reaction tank. This allows the use of a high-pressure-resistant reaction tank, enabling polymerization under high pressure and improving production efficiency. Conversely, if polymerization is carried out without a suspension stabilizer, and a SUS-made reaction tank without anti-adhesion treatment is used, suspended particles may adhere, reducing production efficiency. The concentration of the suspension stabilizer relative to the aqueous medium can be adjusted appropriately according to the conditions.
[0081] When an aqueous dispersion containing a fluoropolymer is obtained through polymerization, the dried fluoropolymer can be recovered by precipitating, washing, and drying the fluoropolymer contained in the aqueous dispersion. Alternatively, when a fluoropolymer is obtained in slurry form through polymerization, the dried fluoropolymer can be recovered by removing the slurry from the reaction vessel and washing and drying it. Drying allows the fluoropolymer to be recovered in powder form.
[0082] Fluorinated copolymers obtained through polymerization can be granulated. There are no particular limitations on the granulation method; existing known methods can be used. For example, methods such as melt extruding the fluorinated copolymer using a single-screw extruder, twin-screw extruder, or tandem extruder, and then cutting it into granules of a specified length, can be used. The extrusion temperature during melt extrusion needs to be varied depending on the melt viscosity of the fluorinated copolymer and the manufacturing method; preferably, it is between the melting point of the fluorinated copolymer and 20°C to 140°C. There are no particular limitations on the cutting method of the fluorinated copolymer; existing known methods such as wire cutting, thermal cutting, underwater cutting, and sheet cutting can be used. The volatile components in the granules can also be removed by heating (degassing treatment). Alternatively, the granules can be treated by contacting them with warm water at 30°C to 200°C, steam at 100°C to 200°C, or hot air at 40°C to 200°C.
[0083] Fluorinated copolymers obtained through polymerization can also be heated to temperatures above 100°C in the presence of air and water (wetting heat treatment). Examples of wetting heat treatment methods include: using an extruder, supplying air and water while melting and extruding the fluorinated copolymer obtained through polymerization. Through wetting heat treatment, thermally unstable functional groups such as -COF and -COOH in the fluorinated copolymer can be converted to the more thermally stable -CF2H, and the total number of -COF and -COOH groups, as well as the total number of carbonyl-containing terminal groups and -CH2OH groups in the fluorinated copolymer, can be easily adjusted to the aforementioned range. Besides air and water, heating the fluorinated copolymer in the presence of an alkali metal salt can promote the conversion reaction to -CF2H. However, it should be noted that contamination from alkali metal salts should be avoided depending on the intended use of the fluorinated copolymer.
[0084] Fluorinated copolymers obtained through polymerization can be fluorinated or left unfluorinated. From the perspective of avoiding time and economic burdens, it is preferable not to fluorinate the fluorinated copolymers. Fluorination can be carried out by contacting the unfluorinated fluorinated copolymer with a fluorinated compound. Through fluorination, the carbonyl-containing terminal groups, thermally unstable functional groups such as -CH2OH, and thermally stable functional groups such as -CF2H in the fluorinated copolymer can be converted into extremely thermally stable -CF3. As a result, the total number of carbonyl-containing terminal groups and -CH2OH in the fluorinated copolymer can be easily adjusted to the aforementioned range.
[0085] As for fluorine-containing compounds, there are no particular limitations; any fluorine radical source that generates fluorine radicals under fluorination conditions can be cited. Examples of such fluorine radical sources include F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, and fluorinated halogens (e.g., IF5, ClF3).
[0086] Fluorine radical sources such as F2 gas can be 100% concentrated, but from a safety perspective, it is preferable to mix them with an inert gas and dilute them to 5% to 50% by mass before use, and more preferably to 15% to 30% by mass. Examples of such inert gases include nitrogen, helium, and argon; from an economic perspective, nitrogen is preferred.
[0087] The conditions for fluorination are not particularly limited; the molten fluorinated copolymer can be brought into contact with the fluorinated compound. However, it is generally carried out at a temperature below the melting point of the fluorinated copolymer, preferably between 20°C and 220°C, and more preferably between 100°C and 200°C. The fluorination treatment is typically carried out for 1 hour to 30 hours, preferably 5 hours to 25 hours. The preferred method of fluorination treatment is to bring the unfluorinated fluorinated copolymer into contact with fluorine gas (F2 gas).
[0088] The fluorinated copolymer of the present invention can also be mixed with other components as needed to obtain a composition. Other components include fillers, plasticizers, processing aids, mold release agents, pigments, flame retardants, lubricants, light stabilizers, weather stabilizers, conductive agents, antistatic agents, ultraviolet absorbers, antioxidants, foaming agents, fragrances, oils, softeners, defluorinated hydrogen agents, etc.
[0089] Examples of fillers include silica, kaolin, clay, organoclay, talc, mica, alumina, calcium carbonate, calcium terephthalate, titanium dioxide, calcium phosphate, calcium fluoride, lithium fluoride, cross-linked polystyrene, potassium titanate, carbon, boron nitride, carbon nanotubes, and glass fiber. Examples of conductive agents include carbon black. Examples of plasticizers include dioctyl phthalate and pentaerythritol. Examples of processing aids include carnauba wax, sulfone compounds, low molecular weight polyethylene, and fluorinated additives. Examples of defluorinating agents include organonium and amidines.
[0090] In addition, other polymers besides the fluorinated copolymers mentioned above can also be used as other components. Examples of other polymers include fluoropolymers, fluororubbers, and non-fluorinated polymers, in addition to the fluorinated copolymers mentioned above.
[0091] Examples of methods for manufacturing the above composition include: dry mixing of the fluorinated copolymer with other components; pre-mixing the fluorinated copolymer with other components using a mixer, followed by melt mixing using a kneader, melt extruder, etc.; etc.
[0092] The fluorinated copolymers or the above-described compositions of the present invention can be used as processing aids, molding materials, etc., and are preferably used as molding materials. Additionally, aqueous dispersions, solutions, suspensions, and copolymer / solvent systems of the fluorinated copolymers of the present invention can be used as coatings, or for encapsulation, impregnation, and film casting. However, due to the aforementioned properties, the fluorinated copolymers of the present invention are preferably used as the above-described molding materials.
[0093] The fluorinated copolymer of the present invention or the above composition can also be molded to obtain a molded body.
[0094] The method for molding the above-mentioned fluorinated copolymer or composition is not particularly limited, and examples include injection molding, extrusion molding, compression molding, blow molding, transfer molding, rotational molding, and roll forming. Among these molding methods, extrusion molding, compression molding, injection molding, or transfer molding are preferred, and injection molding, extrusion molding, or transfer molding are more preferred because they can produce molded articles with high productivity; injection molding is even more preferred. That is, as the molded article, an extruded molded article, a compression molded article, an injection molded article, or a transfer molded article is preferred, and injection molded articles, extrusion molded articles, or transfer molded articles are more preferred because they can be produced with high productivity; injection molded articles are even more preferred. By molding the fluorinated copolymer of the present invention using injection molding, a beautiful molded article can be obtained.
[0095] As molded bodies containing the fluorinated copolymer of the present invention, they can be, for example, nuts, bolts, joints, membranes, bottles, washers, wire sheaths, tubes, hoses, pipes, valves, plates, seals, gaskets, cans, rollers, containers, stopcocks, connectors, filter housings, filter covers, flow meters, pumps, wafer carriers, wafer boxes, etc.
[0096] The fluorinated copolymers, the above-described compositions, or the above-described molded articles of the present invention can be used for, for example, the following applications.
[0097] Food packaging films, lining materials for fluid transport pipelines used in food manufacturing processes, gaskets, sealing materials, thin sheets, and other fluid transport components for food manufacturing equipment;
[0098] Chemical stoppers, packaging films, lining materials for fluid delivery pipelines used in chemical manufacturing processes, gaskets, sealing materials, thin plates, and other reagent delivery components;
[0099] Inner lining components for chemical equipment and semiconductor plants' liquid tanks and piping;
[0100] O-rings / pipes / gaskets, valve core materials, hoses, sealing materials, etc. used in the fuel system and peripheral devices of automobiles; hoses, sealing materials, and other fuel delivery components used in the AT system of automobiles.
[0101] The carburetor flange gaskets, shaft seals, valve stem seals, sealing materials, hoses, etc. used in the engine and peripheral devices of automobiles; brake hoses, air conditioning hoses, radiator hoses, wire sheathing materials, and other automobile components.
[0102] O-rings, tubes, gaskets, valve core materials, hoses, sealing materials, rollers, washers, diaphragms, connectors and other chemical delivery components for semiconductor manufacturing equipment;
[0103] Coating and ink components for coating equipment, such as coating rollers, hoses, tubes, and ink containers;
[0104] Food and beverage conduits, hoses, belts, gaskets, connectors and other food and beverage conveying components, food packaging materials, and glass cooking equipment;
[0105] Pipes, hoses, and other components used for waste liquid transportation;
[0106] Pipes, hoses, and other components used for high-temperature liquid transfer;
[0107] Pipes, hoses and other components used in steam piping;
[0108] Corrosion-resistant tape for piping, such as tape wrapped around the deck of a ship;
[0109] Various coating materials, such as wire coating materials, optical fiber coating materials, transparent surface coating materials and backing agents applied to the light incident side of photovoltaic elements in solar cells;
[0110] The diaphragm and various sliding components such as gaskets in a diaphragm pump;
[0111] Weather-resistant covers for agricultural films, various roofing materials, and sidewalls;
[0112] Interior materials used in the construction industry, and glass-like covering materials such as non-combustible fire-resistant safety glass;
[0113] Lining materials such as laminated steel sheets used in the home appliance industry.
[0114] Further examples of fuel delivery components used in the fuel systems of the aforementioned automobiles include fuel hoses, filler hoses, and evaporator hoses. These fuel delivery components can also be used for fuels resistant to acidic gasoline, alcohol-based fuels, and fuels containing gasoline additives such as those resistant to methyl tert-butyl ether and amines.
[0115] The aforementioned chemical stoppers and packaging films exhibit excellent chemical resistance to acids and other chemicals. Additionally, anti-corrosion tape wrapped around the piping of chemical equipment can also be cited as a component for transporting the aforementioned chemical solutions.
[0116] Examples of the aforementioned molded bodies include automobile radiator water chambers, medicine tanks, bellows, partitions, rollers, gasoline tanks, waste liquid conveying containers, high-temperature liquid conveying containers, and fish farming and aquaculture tanks.
[0117] Further examples of the molded bodies mentioned above include components used in automobile bumpers, door panels, dashboards, food processing devices, cooking machines, waterproof and oil-proof glass, lighting-related instruments, indicator panels and housings of OA instruments, electrically illuminated signboards, displays, LCD screens, mobile phones, printer chassis, electrical and electronic components, groceries, trash cans, bathtubs, prefabricated bathrooms, exhaust fans, lighting frames, etc.
[0118] Molded articles containing the fluorinated copolymer of the present invention exhibit excellent abrasion resistance at 80°C, solvent crack resistance, rigidity at 100°C, and durability under repeated loads, making them suitable for use in bolts, filter covers, pipes, membranes, or wire coatings, etc.
[0119] Molded articles containing the fluorinated copolymers of the present invention are suitable for use as compressed components such as gaskets and seals. The compressed components of the present invention can be gaskets or seals.
[0120] The size and shape of the compressed member of the present invention can be appropriately set according to the application and are not particularly limited. The shape of the compressed member of the present invention can be, for example, ring-shaped. In addition, the compressed member of the present invention can have a circular, elliptical, or quadrilateral shape with rounded corners when viewed from above, and has a through hole in its central part.
[0121] The compressed member of the present invention is preferably used as a component for constructing a non-aqueous electrolyte battery. The compressed member of the present invention is particularly suitable as a component used in a state of contact with the non-aqueous electrolyte in a non-aqueous electrolyte battery. That is, the compressed member of the present invention can have a liquid-contacting surface for contact with the non-aqueous electrolyte in a non-aqueous electrolyte battery.
[0122] As for non-aqueous electrolyte batteries, there are no particular limitations as long as the battery contains a non-aqueous electrolyte; examples include lithium-ion secondary batteries and lithium-ion capacitors. Furthermore, components constituting non-aqueous electrolyte batteries include sealing components and insulating components.
[0123] The non-aqueous electrolyte is not particularly limited and can be one or more of the following known solvents: propylene carbonate, ethylene carbonate, butyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate. The non-aqueous electrolyte battery may further include an electrolyte. The electrolyte is not particularly limited and can be LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, etc.
[0124] The compressed component of the present invention can preferably be used as a sealing component such as a sealing gasket or sealing pad, or an insulating component such as an insulating gasket or insulating pad. A sealing component is used to prevent leakage of liquid or gas or intrusion of liquid or gas from the outside. An insulating component is used for electrical insulation. The compressed component of the present invention can also be used for both sealing and insulation purposes.
[0125] The compressed member of the present invention is suitable for use as a sealing member or an insulating member for non-aqueous electrolyte batteries. Furthermore, the compressed member of the present invention, due to containing the aforementioned fluorinated copolymer, exhibits excellent insulating properties. Therefore, when the compressed member of the present invention is used as an insulating member, it securely seals with two or more conductive members, preventing short circuits over a long period.
[0126] The fluorinated copolymer of the present invention is suitable for use as a material for forming wire coatings. Wires having a coating layer containing the fluorinated copolymer of the present invention exhibit almost no change in outer diameter, thus resulting in excellent electrical properties.
[0127] The coated wire has a core wire and a coating layer disposed around the core wire containing the fluorinated copolymer of the present invention. For example, the coating layer can be an extruded body formed by melt extrusion molding of the fluorinated copolymer of the present invention onto the core wire. The coated wire is suitable for LAN cables (Ethernet cables), high-frequency transmission cables, flat cables, heat-resistant cables, etc., and is particularly suitable for transmission cables such as LAN cables (Ethernet cables) and high-frequency transmission cables.
[0128] The core wire material can be a metallic conductor such as copper or aluminum. The core wire diameter is preferably 0.02 mm to 3 mm. More preferably, the core wire diameter is 0.04 mm or more, even more preferably 0.05 mm or more, and particularly preferably 0.1 mm or more. Even more preferably, the core wire diameter is 2 mm or less.
[0129] Specific examples of core wires include AWG (American wire gauge)-46 (solid copper wire with a diameter of 40μm), AWG-26 (solid copper wire with a diameter of 404μm), AWG-24 (solid copper wire with a diameter of 510μm), and AWG-22 (solid copper wire with a diameter of 635μm).
[0130] The thickness of the coating layer is preferably 0.1 mm to 3.0 mm. The thickness of the coating layer is also preferably less than 2.0 mm.
[0131] Coaxial cables are an example of high-frequency transmission cables. Coaxial cables typically have a structure consisting of an inner conductor, an insulating sheath, an outer conductor layer, and a protective sheath layer layered sequentially from the core to the outer periphery. Molded bodies containing the fluorinated copolymer of the present invention can be suitable as insulating sheaths containing the fluorinated copolymer. The thickness of each layer in the above structure is not particularly limited; typically, the diameter of the inner conductor is about 0.1 mm to 3 mm, the thickness of the insulating sheath is about 0.3 mm to 3 mm, the thickness of the outer conductor layer is about 0.5 mm to 10 mm, and the thickness of the protective sheath is about 0.5 mm to 2 mm.
[0132] The coating may contain air bubbles, which are preferably evenly distributed in the coating.
[0133] The average bubble diameter is not limited, but is preferably 60 μm or less, more preferably 45 μm or less, even more preferably 35 μm or less, even more preferably 30 μm or less, particularly preferably 25 μm or less, and especially preferably 23 μm or less. Furthermore, the average bubble diameter is preferably 0.1 μm or more, more preferably 1 μm or more. The average bubble diameter can be obtained by acquiring an electron microscope image of the wire cross-section, calculating the diameter of each bubble using image processing, and then averaging the results.
[0134] The foaming rate of the coating layer can be 20% or more. More preferably, it is 30% or more, further preferably 33% or more, and even more preferably 35% or more. There is no particular upper limit, for example, 80%. The upper limit of the foaming rate can be 60%. The foaming rate is calculated as ((specific gravity of wire coating material - specific gravity of coating layer) / specific gravity of wire coating material) × 100. The foaming rate can be adjusted appropriately according to the application, for example, by adjusting the gas insertion amount in the extruder described later, or by selecting the type of dissolved gas.
[0135] The coated wire may also have other layers between the core wire and the coating layer, and may further have other layers (outer layers) around the coating layer. If the coating layer contains air bubbles, the wire of the present invention may also be a two-layer structure (outer sheath-foam) with a non-foamed layer inserted between the core wire and the coating layer; a two-layer structure (foam-outer sheath) with a non-foamed layer on the outer layer; and a three-layer structure (outer sheath-foam-outer sheath) with a non-foamed layer on the outer layer of the outer sheath-foam. The non-foamed layer is not particularly limited and may be a resin layer composed of TFE / HFP copolymers, TFE / PAVE copolymers, TFE / ethylene copolymers, vinylidene fluoride polymers, polyolefin resins such as polyethylene [PE], and resins such as polyvinyl chloride [PVC].
[0136] Coated wires can be manufactured, for example, by heating a fluorinated copolymer using an extruder and extruding it onto the core wire while the fluorinated copolymer is in a molten state to form a coating.
[0137] During the formation of the coating layer, the fluorinated copolymer can also be heated, and a gas can be introduced into the fluorinated copolymer while it is in a molten state to form the aforementioned coating layer containing bubbles. The gas can be, for example, dichlorofluoromethane, nitrogen, carbon dioxide, or a mixture of these gases. The gas can be introduced into the heated fluorinated copolymer as a pressurized gas, or it can be generated by mixing a chemical foaming agent into the fluorinated copolymer. The gas dissolves in the molten fluorinated copolymer.
[0138] In addition, the fluorinated copolymer of the present invention is suitable for use as a material in products for high-frequency signal transmission.
[0139] As for the aforementioned high-frequency signal transmission products, there are no particular limitations as long as the product is used for high-frequency signal transmission. Examples include (1) molded boards such as insulating boards for high-frequency circuits, insulating materials for connecting components, and printed wiring boards; (2) molded bodies such as bases and radomes for high-frequency vacuum tubes; and (3) covered wires such as coaxial cables and LAN cables. The aforementioned high-frequency signal transmission products are suitable for use in satellite communication equipment, mobile phone base stations, and other equipment that utilizes microwaves, especially microwaves from 3 GHz to 30 GHz.
[0140] In the aforementioned high-frequency signal transmission products, the fluorinated copolymer of the present invention is suitable for use as an insulator due to its low dielectric loss tangent.
[0141] As for the molded plate described in (1) above, a printed wiring substrate is preferred from the perspective of obtaining good electrical characteristics. There are no particular limitations on the printed wiring substrate described above; examples include printed wiring substrates for electronic circuits in mobile phones, various computers, and communication devices. As for the molded body described in (2) above, an antenna radome is preferred from the perspective of low dielectric loss.
[0142] The fluorinated copolymers of the present invention are suitable for use in membranes.
[0143] The film of the present invention is useful as a release film. The release film can be manufactured by molding the fluorinated copolymer of the present invention through melt extrusion molding, calendering, compression molding, casting, etc. From the viewpoint of obtaining a uniform film, the release film can be manufactured by melt extrusion molding.
[0144] The membrane of this invention can be applied to the surface of rollers used in OA equipment. Furthermore, the fluorinated copolymer of this invention can be molded into necessary shapes, such as sheets, films, or tubes, through extrusion molding, compression molding, or pressing, for use as a surface material for OA equipment rollers or belts. In particular, thin-walled tubes and membranes can be manufactured using melt extrusion molding.
[0145] The fluorinated copolymers of the present invention are also suitable for use in tubes, bottles, etc.
[0146] The embodiments have been described above, but it is understood that various changes can be made to the methods and details without departing from the spirit and scope of the claims.
[0147] Example
[0148] Next, embodiments will be given to illustrate the implementation of the present invention, but the present invention is not limited to the embodiments described.
[0149] The values in the examples were measured using the following methods.
[0150] (Monomer content)
[0151] The content of each monomer unit in the fluorinated copolymer was determined using an NMR analyzer (e.g., Bruker BioSpin, AVANCE300 high-temperature probe) or an infrared absorption analyzer (Perkin Elmer, Spectrum One).
[0152] (Mel flow rate (MFR))
[0153] Regarding the MFR of fluorinated copolymers, according to ASTM D-1238, the mass (g / 10 min) of polymer flowing out of a die with an inner diameter of 2 mm and a length of 8 mm is measured every 10 minutes using a melt flow index tester G-01 (manufactured by Toyo Seiki Co., Ltd.) at 372°C and a load of 5 kg, and the MFR is calculated accordingly.
[0154] (Quantity of -CF2H)
[0155] The number of -CF2H groups in the fluorinated copolymer was determined using an AVANCE-300 nuclear magnetic resonance (NMR) system (manufactured by Bruker BioSpin) at a temperature set to (polymer melting point + 20) °C. 19 The value was determined by F-NMR analysis and obtained from the peak integral of the -CF2H group.
[0156] (The number of -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2)
[0157] The dried powders or granules obtained in the examples and comparative examples were cold-pressed to form films with a thickness of 0.25 mm to 0.3 mm. The films were analyzed by scanning them 40 times using a Fourier transform infrared spectroscopy (FT-IR) device (Spectrum One, PerkinElmer). The obtained infrared absorption spectra were compared with those of known films to determine the types of terminal groups. Furthermore, based on the absorption peaks of specific functional groups appearing in the differential spectrum between the obtained and known films, the concentration of each 1 × 10⁻⁶ functional group in the sample was calculated according to the following formula (A). 6 The number of functional groups N per carbon atom.
[0158] N = I × K / t (A)
[0159] I: Absorbance
[0160] K: Correction coefficient
[0161] t: Membrane thickness (mm)
[0162] For reference, the absorption frequencies, molar absorptivity, and correction factors for the functional groups in the examples are shown in Table 2. Furthermore, the molar absorptivity was determined using FT-IR measurement data from the low-molecular-weight model compounds.
[0163] [Table 2]
[0164] Table 2
[0165]
[0166] (the number of -OC(=O)OR(carbonate groups))
[0167] Analysis was performed using the method described in International Publication No. 2019 / 220850. The absorption frequency was set to 1817 cm⁻¹. -1 The molar absorbance coefficient was set to 170 (l / cm / mol), and the correction coefficient was set to 1426. Otherwise, the number of -OC(=O)OR (carbonate groups) was calculated in the same way as the number of functional groups N.
[0168] (Melting point)
[0169] Regarding the melting point of the fluorinated copolymer, a differential scanning calorimeter (trade name: X-DSC7000, manufactured by Hitachi High-Tech Science) was used to perform a first heating from 200°C to 350°C at a heating rate of 10°C / min. Then, the temperature was cooled from 350°C to 200°C at a cooling rate of 10°C / min. A second heating was then performed from 200°C to 350°C at a heating rate of 10°C / min. The melting point was determined from the peak value of the melting curve generated during the second heating process.
[0170] Comparative Example 1
[0171] 40.25 kg of deionized water and 0.189 kg of methanol were added to a 174 L autoclave equipped with a stirrer, and the autoclave was thoroughly purged with nitrogen under vacuum. Then, the autoclave was degassed under vacuum, and 40.25 kg of HFP and 0.48 kg of PPVE were added to the vacuum-sealed autoclave. The autoclave was then heated to 30.0 °C. Next, TFE was added until the internal pressure of the autoclave reached 0.911 MPa. Then, 0.63 kg of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to begin polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.911 MPa, and this pressure was maintained by continuously adding TFE. 0.189 kg of methanol was added 1.5 hours after the start of polymerization. Two hours after the start of polymerization, 0.63 kg of DHP was added, and four hours later, with the internal pressure reduced by 0.001 MPa. Six hours later, 0.48 kg of DHP was added, with the internal pressure reduced by 0.001 MPa each time. Thereafter, 0.13 kg of DHP was added every two hours until the reaction was complete, with the internal pressure reduced by 0.001 MPa each time.
[0172] It should be noted that 0.14 kg of PPVE was added at the points when the TFE addition reached 8.1 kg, 16.2 kg, and 24.3 kg, respectively. Additionally, 0.189 kg of methanol was added to the autoclave at the points when the TFE addition reached 6.0 kg and 18.1 kg, respectively. The polymerization was terminated when the TFE addition reached 40.25 kg. After polymerization, unreacted TFE and HFP were released, yielding a wet powder. This wet powder was then washed with pure water and dried at 150°C for 10 hours to obtain 46.2 kg of dry powder.
[0173] The obtained powder was melt-extruded at 370°C using a screw extruder (trade name: PCM46, manufactured by Chibei Co., Ltd.) to obtain copolymer granules. The obtained granules were then used to determine various physical properties using the method described above. The results are shown in Table 3.
[0174] Comparative Example 2
[0175] 40.25 kg of deionized water and 0.330 kg of methanol were added to a 174 L autoclave equipped with a stirrer, and the autoclave was thoroughly purged with nitrogen under vacuum. Afterward, the autoclave was degassed under vacuum, and 40.25 kg of HFP and 0.66 kg of PPVE were added to the vacuum-sealed autoclave. The autoclave was then heated to 25.5 °C. Next, TFE was added until the internal pressure of the autoclave reached 0.843 MPa. Then, 1.25 kg of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to begin polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.843 MPa, and this pressure was maintained by continuously adding TFE. 0.330 kg of methanol was added 1.5 hours after the start of polymerization. Two hours after the start of polymerization, 1.25 kg of DHP was added, and four hours later, with the internal pressure reduced by 0.002 MPa. Six hours later, 0.96 kg of DHP was added, with the internal pressure reduced by 0.002 MPa each time. Thereafter, 0.25 kg of DHP was added every two hours until the reaction was complete, with the internal pressure reduced by 0.002 MPa each time.
[0176] It should be noted that 0.17 kg of PPVE was added at the points when the TFE addition reached 8.1 kg, 16.2 kg, and 24.3 kg, respectively. Additionally, 0.330 kg of methanol was added to the autoclave at the points when the TFE addition reached 6.0 kg and 18.1 kg, respectively. The polymerization was terminated when the TFE addition reached 40.25 kg. After polymerization, unreacted TFE and HFP were released, yielding a wet powder. This wet powder was then washed with pure water and dried at 150°C for 10 hours to obtain 45.4 kg of dry powder.
[0177] The obtained powder was melt-extruded at 370°C using a screw extruder (trade name: PCM46, manufactured by Chibei Co., Ltd.) to obtain copolymer granules. The obtained granules were then used to determine various physical properties using the method described above. The results are shown in Table 3.
[0178] Comparative Example 3
[0179] 40.25 kg of deionized water and 0.247 kg of methanol were added to a 174 L autoclave equipped with a stirrer, and the autoclave was thoroughly purged with nitrogen under vacuum. Afterward, the autoclave was degassed under vacuum, and 40.25 kg of HFP and 0.78 kg of PPVE were added to the vacuum-sealed autoclave. The autoclave was then heated to 32.0 °C. Next, TFE was added until the internal pressure of the autoclave reached 0.923 MPa. Then, 0.31 kg of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to begin polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.923 MPa, and this pressure was maintained by continuously adding TFE. 0.247 kg of methanol was added 1.5 hours after the start of polymerization. Two hours after the start of polymerization, 0.31 kg of DHP was added, and four hours later, with the internal pressure reduced by 0.001 MPa. Six hours later, 0.24 kg of DHP was added, with the internal pressure reduced by 0.001 MPa. Thereafter, 0.07 kg of DHP was added every two hours until the reaction was complete.
[0180] It should be noted that 0.17 kg of PPVE was added at the points when the TFE addition reached 8.1 kg, 16.2 kg, and 24.3 kg, respectively. Additionally, 0.247 kg of methanol was added to the autoclave at the points when the TFE addition reached 6.0 kg and 18.1 kg, respectively. The polymerization was terminated when the TFE addition reached 40.25 kg. After polymerization, unreacted TFE and HFP were released, yielding a wet powder. This wet powder was then washed with pure water and dried at 150°C for 10 hours to obtain 47.5 kg of dry powder.
[0181] The obtained powder was melt-extruded at 370°C using a screw extruder (trade name: PCM46, manufactured by Chibei Co., Ltd.) to obtain copolymer granules. The obtained granules were then used to determine various physical properties using the method described above. The results are shown in Table 3.
[0182] Comparative Example 4
[0183] The amount of methanol added before polymerization was changed to 0.286 kg, and the amount of methanol added in batches after polymerization began was also changed to 0.286 kg each time. The amount of PPVE added before polymerization was changed to 0.52 kg, and the amount of PPVE added in batches after polymerization began was also changed to 0.15 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.911 MPa. Otherwise, copolymer granules were obtained in the same manner as in Comparative Example 1. Using the obtained granules, various physical properties were measured using the methods described above. The results are shown in Table 3.
[0184] Comparative Example 5
[0185] The amount of methanol added before polymerization was changed to 0.259 kg, and the amount of methanol added in batches after polymerization was started was also changed to 0.259 kg each time. The amount of PPVE added before polymerization was changed to 0.36 kg, and the amount of PPVE added in batches after polymerization was also changed to 0.11 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.905 MPa. Otherwise, copolymer granules were obtained in the same manner as in Comparative Example 1. Using the obtained granules, various physical properties were measured using the above method. The results are shown in Table 3.
[0186] Comparative Example 6
[0187] The amount of methanol added before polymerization was changed to 0.158 kg, and the amount of methanol added in batches after polymerization began was also changed to 0.158 kg each time. The amount of PPVE added before polymerization was changed to 0.70 kg, and the amount of PPVE added in batches after polymerization began was also changed to 0.22 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.897 MPa. Otherwise, copolymer granules were obtained in the same manner as in Comparative Example 1. The HFP and PPVE contents were determined using the obtained granules by the above method. The results are shown in Table 3.
[0188] The obtained granules were degassed in an electric furnace at 200°C for 72 hours, then placed in a VVD-30 vacuum vibratory reactor (manufactured by Okawahara Manufacturing Co., Ltd.), and heated to 110°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, a temporary vacuum was applied, and F2 gas was introduced again. This process was repeated 0.5 hours later, followed by another vacuum and introduction of F2 gas. This process of introducing F2 gas and evacuating the vacuum was repeated every hour, and the reaction was carried out at 110°C for 8 hours. After the reaction was completed, the reactor was completely replaced with N2 gas to stop the fluorination reaction and obtain the granules. Various physical properties of the obtained granules were measured using the above method. The results are shown in Table 3.
[0189] Comparative Example 7
[0190] 945g of deionized water and 4.7g of methanol were added to a 4L autoclave equipped with a stirrer, and the autoclave was thoroughly purged with nitrogen. Then, the autoclave was degassed under vacuum, and 945g of HFP and 9.8g of PEVE were added to the vacuum-sealed autoclave. The autoclave was then heated to 30.0°C. Next, TFE was added until the internal pressure of the autoclave reached 0.900MPa. Then, 14.7g of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to begin polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.900MPa, and this pressure was maintained by continuously adding TFE. 4.7g of methanol was added 1.5 hours after the start of polymerization. Two hours and four hours after the start of polymerization, 14.7 g of DHP was added, and the internal pressure was reduced by 0.001 MPa. Six hours later, 11.3 g was added, and the internal pressure was reduced by 0.001 MPa. Thereafter, 3.0 g of DHP was added every two hours until the reaction was completed, and the internal pressure was reduced by 0.001 MPa each time.
[0191] It should be noted that 3.1g of PEVE was added at the points where TFE was continuously added to 190g and 380g, respectively. Additionally, 4.7g of methanol was added to the autoclave when TFE was added to 140g. The polymerization was terminated when TFE was added to 454g. After polymerization, unreacted TFE and HFP were released, yielding a wet powder. This wet powder was then washed with pure water and dried at 150℃ for 10 hours to obtain 526g of dry powder.
[0192] The obtained powder is used The copolymer granules were obtained by melt extrusion at 370°C using a screw extruder (manufactured by Imoto Manufacturing Co., Ltd.). Various physical properties of the obtained granules were measured using the methods described above. The results are shown in Table 3.
[0193] Example 1
[0194] The amount of methanol added before polymerization was changed to 0.252 kg, and the amount of methanol added in batches after polymerization began was also changed to 0.252 kg each time. The amount of PPVE added before polymerization was changed to 0.56 kg, and the amount of PPVE added in batches after polymerization began was also changed to 0.17 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.914 MPa. Otherwise, copolymer granules were obtained in the same manner as in Comparative Example 1. The HFP and PPVE contents were determined using the obtained granules by the above method. The results are shown in Table 3.
[0195] The obtained granules were degassed in an electric furnace at 200°C for 8 hours, then placed in a VVD-30 vacuum vibratory reactor (manufactured by Okawahara Seisakusho Co., Ltd.), and heated to 200°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, a temporary vacuum was applied, and F2 gas was introduced again. This process was repeated 0.5 hours later, followed by another vacuum and introduction of F2 gas. This process of introducing F2 gas and evacuating the vacuum was repeated every hour, and the reaction was carried out at 200°C for 8 hours. After the reaction, the reactor was completely replaced with N2 gas to terminate the fluorination reaction, yielding granules. Various physical properties of the obtained granules were measured using the above method. The results are shown in Table 3.
[0196] Example 2
[0197] The amount of methanol added before polymerization was changed to 0.242 kg, and the amount of methanol added in batches after polymerization began was also changed to 0.242 kg each time. The amount of PPVE added before polymerization was changed to 0.47 kg, and the amount of PPVE added in batches after polymerization began was also changed to 0.14 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.905 MPa. Otherwise, copolymer granules were obtained in the same manner as in Comparative Example 1. Various physical properties were measured using the obtained granules according to the above method. The results are shown in Table 3.
[0198] Example 3
[0199] The amount of methanol added before polymerization was changed to 0.214 kg, and the amount of methanol added in batches after polymerization was started was also changed to 0.214 kg each time. The amount of PPVE added before polymerization was changed to 0.42 kg, and the amount of PPVE added in batches after polymerization was also changed to 0.13 kg each time. The set pressure inside the autoclave before and after polymerization was changed to 0.897 MPa. Otherwise, copolymer granules were obtained in the same manner as in Comparative Example 1. Using the obtained granules, various physical properties were measured by the above method. The results are shown in Table 3.
[0200] [Table 3]
[0201] Table 3
[0202]
[0203] Table 3 shows "Other (number / C10)" 6 The notation “)” indicates the total number of -COOCH3, -CF=CF2, and -CONH2. The notation “<9” in Table 3 means the number (total) of -CF2H groups is less than 9. The notation “<6” in Table 3 means the number (total) of the target functional group is less than 6. The notation “ND” in Table 3 indicates a peak for which quantification could not be achieved.
[0204] Next, the obtained granules were used to evaluate the following properties. The results are shown in Table 4.
[0205] (Abrasion test)
[0206] Using a granulation and hot-press molding machine, sheet-shaped test pieces with a thickness of approximately 0.2 mm were prepared, from which 10 cm × 10 cm test pieces were cut. The prepared test pieces were fixed on the test bench of a Tiber abrasion testing machine (No. 101 Special Type Tiber Abrasion Testing Machine, manufactured by Yasuda Seiki Co., Ltd.). Abrasion tests were conducted using the Tiber abrasion testing machine under the following conditions: test piece surface temperature 80°C, load 500 g, abrasion wheel CS-10 (grinding with #240 abrasive paper for 20 revolutions), and rotation speed 60 rpm. The weight of the test piece was measured after 1000 revolutions, and the same test piece was further tested after 4000 revolutions, and the weight of the test piece was measured again. The abrasion amount was calculated using the following formula.
[0207] Wear amount (mg) = M1 - M2
[0208] M1: Weight of the test piece after 1000 revolutions (mg)
[0209] M2: Weight of the test piece (mg) after 4000 revolutions.
[0210] (Crack test caused by chemical immersion)
[0211] Sheet-shaped molded bodies with a thickness of approximately 2 mm were produced using granulation and a thermoforming machine. The resulting sheets were punched using a 13.5 mm × 38 mm rectangular dumbbell, yielding three test pieces. A 19 mm × 0.45 mm notch was cut at the center of the long side of each test piece according to ASTM D1693. The three notched test pieces and 25 g of ethylene glycol were placed in a 100 mL polypropylene bottle and heated at 150°C for 20 hours. The notched test pieces were then removed. The three notched test pieces were mounted in a stress cracking test fixture according to ASTM D1693 and heated at 180°C for 2 hours. The notches and their surrounding areas were visually observed, and the number of cracks was counted. Sheets that did not crack exhibited excellent solvent cracking resistance.
[0212] ○: The number of cracks is 0
[0213] ×: The number of cracks is more than 1.
[0214] (Deflection under load at 100℃)
[0215] Using granulation and a hot press, sheet-like test pieces with a thickness of approximately 4.0 mm were prepared. 80 × 10 mm test pieces were cut from these pieces and heated in an electric furnace at 100°C for 20 hours. In addition to using the obtained test pieces, tests were conducted according to the method described in JIS K-K7191-1 using a heat distortion tester (manufactured by Yasuda Seiki Co., Ltd.) under the conditions of a test temperature of 30°C to 150°C, a heating rate of 120°C / hour, a bending stress of 1.8 MPa, and the flatwise method. The load deflection was calculated using the following formula. Sheets with low load deflection at 100°C exhibit excellent rigidity at 100°C.
[0216] Load-induced deflection (%) = a2 / a1 × 100
[0217] a1: Thickness of the test piece before the test (mm)
[0218] a2: Deflection at 100℃ (mm)
[0219] (Tensile creep test)
[0220] Tensile creep strain was determined using a Hitachi High-Tech TMA-7100. Sheets approximately 0.1 mm thick were prepared using a granulator and thermoforming machine. Samples 2 mm wide and 22 mm long were then fabricated from these sheets. The samples were mounted in the measuring fixture with a 10 mm gap between the clamps. A cross-sectional load of 4.88 N / mm² was applied to the samples. 2The sample was subjected to a load and placed at 100°C. The displacement (mm) of the sample length was measured from 90 minutes to 1050 minutes after the start of the test. The ratio of the displacement (mm) to the initial sample length (10mm) was calculated (tensile creep strain (%)). Samples with low tensile creep strain (%) measured at 100°C for 1050 minutes do not easily elongate even under prolonged tensile loads in high-temperature environments, demonstrating excellent high-temperature tensile creep resistance (100°C).
[0221] (Tensile strength after 8,000 cycles)
[0222] Tensile strength after 8,000 cycles was determined using a Shimadzu MMT-250NV-10 fatigue testing machine. A pellet approximately 2.4 mm thick was prepared using a granulator and thermoforming machine. A dumbbell-shaped sample (2.4 mm thickness, 5.0 mm width, and 22 mm measuring section length) was fabricated using ASTM D1708 micro-dumbbells. The sample was mounted in the testing fixture, which was then placed in a 110°C thermostatic bath with the sample mounted. Uniaxial tension was repeatedly applied at a stroke of 0.2 mm and a frequency of 100 Hz, and the tensile strength (tensile strength at a stroke of +0.2 mm, unit: N) was measured for each tension.
[0223] The sheet with high tensile strength after 8,000 cycles maintains high tensile strength even after being subjected to 8,000 loads, and has excellent durability under repeated loads (110°C).
[0224] (Injection molding)
[0225] ·condition
[0226] The copolymer was injection molded using an injection molding machine (Sumitomo Heavy Industries, Ltd., SE50EV-A) with a barrel temperature of 385°C, a mold temperature of 180°C, and an injection speed of 20 mm / s. A Cr-plated mold (100 mm × 100 mm × 2.0 mm, thin-film gate, flow length from the gate 100 mm) was used for HPM38. The resulting injection-molded body was observed and evaluated according to the following criteria: Visual inspection was performed to check for any white opacity. The presence or absence of surface roughness was confirmed by contacting the surface of the injection-molded body.
[0227] 3: The injection-molded part is transparent throughout and has a smooth surface.
[0228] 2: A white cloudiness was observed within 1 cm of the gate of the mold, and the surface was smooth overall.
[0229] 1: A white cloudiness was observed within 1 cm of the location of the mold gate, and a rough surface was confirmed within 1 cm of the location of the mold gate.
[0230] 0: The copolymer is not filled in the mold, and the desired shape of the molded body cannot be obtained.
[0231] (Conditions for wire coating)
[0232] use A wire coating extrusion molding machine (manufactured by Tanabe Plastics Machinery Co., Ltd.) extrudes a fluorinated copolymer onto a copper conductor with a conductor diameter of 0.50 mm to obtain a coated wire at the following coating thickness. The wire coating extrusion molding conditions are as follows.
[0233] a) Core conductor: Conductor diameter 0.50mm
[0234] b) Coating thickness: 0.20mm
[0235] c) Diameter of the covered wire: 0.90mm
[0236] d) Wire pulling speed: 70m / min
[0237] e) Extrusion conditions:
[0238] • Single-screw extrusion molding machine with a barrel shaft diameter of 30mm and an L / D ratio of 22
[0239] • Mold (inner diameter) / piece (outer diameter) = 9.0mm / 5.0mm
[0240] Extruder set temperatures: Barrel section C-1 (320℃), Barrel section C-2 (350℃), Barrel section C-3 (370℃), Head H (380℃), Die head D-1 (380℃), Die head D-2 (380℃). Core wire preheating is set to 80℃.
[0241] (Cover disconnected)
[0242] The coating process for wires is carried out continuously. If the coating breaks more than once within 1 hour, it is considered that the process is not continuous (×), and if the coating does not break, it is considered that the process is continuous (○).
[0243] (spark)
[0244] A DENSOK HIGH FREQ SPARK TESTER was installed online on the wire sheath to evaluate for any defects in the wire sheath at 1500V. The molding process was continued for 1 hour, and the number of sparks was counted.
[0245] (Membrane forming properties)
[0246] use An extruder (manufactured by Imoto Manufacturing Co., Ltd.) and a T-die are used to shape the granules into a film. The extrusion molding conditions are as follows.
[0247] a) Winding speed: 1m / minute
[0248] b) Roller temperature: 120℃
[0249] c) Membrane width: 70mm
[0250] d) Thickness: 0.10mm
[0251] e) Extrusion conditions:
[0252] • Single-screw extrusion molding machine with a barrel shaft diameter of 14mm and an L / D ratio of 20
[0253] Extruder set temperatures: Barrel section C-1 (330℃), Barrel section C-2 (350℃), Barrel section C-3 (365℃), T-die head (370℃)
[0254] The extrusion molding of the fluorinated copolymer continues until the fluorinated copolymer is stably extruded from the molding machine. Next, a film with a length of 11 m or more (70 mm wide) is produced by extruding the fluorinated copolymer to a thickness of 0.10 mm. A 10-11 m portion is cut from the end of the obtained film to prepare a test piece (1 m long, 70 mm wide) for measuring thickness variation. The thickness is measured at three locations: the center point in the width direction at the end of the film and two locations 25 mm away from that center point in the width direction. Furthermore, the thickness is measured at nine locations: three center points spaced 25 cm apart from the center point at one end of the film towards the other end, and two locations 25 mm away from each center point in the width direction. Of the total 12 measurements, those with 1 or fewer measurements outside the ±10% range of 0.10 mm are designated as ○, and those with 2 or more measurements outside the ±10% range of 0.10 mm are designated as ×.
[0255]
Claims
1. A fluorinated copolymer, comprising tetrafluoroethylene units, hexafluoropropylene units, and perfluoro(propyl vinyl ether) units, wherein, The content of tetrafluoroethylene units relative to all monomer units is 86.2%–88.5% by mass. The content of hexafluoropropylene units relative to all monomer units is 10.3%–12.2% by mass. The content of perfluoro(propyl vinyl ether) units is 1.2% to 1.6% by mass relative to all monomer units. The melt flow rate at a load of 5 kg and a temperature of 372 °C is 13.0 g / 10 min to 17.0 g / 10 min.
2. The fluorinated copolymer as described in claim 1, wherein, The content of hexafluoropropylene units is 10.7% to 11.5% by mass relative to all monomer units.
3. The fluorinated copolymer as described in claim 1 or 2, wherein, The content of perfluoro(propyl vinyl ether) units is 1.2% to 1.5% by mass relative to all monomer units.
4. The fluorinated copolymer as described in claim 1 or 2, wherein, The melt flow rate at a load of 5 kg and a temperature of 372 °C is 14.1 g / 10 min to 16.0 g / 10 min.
5. The fluorinated copolymer as described in claim 1 or 2, wherein, The amount of -CF2H relative to every 10 6 Each main chain has more than 50 carbon atoms.
6. The fluorinated copolymer as described in claim 1 or 2, wherein, The total number of carbonyl-containing terminal groups, -CF=CF2, and -CH2OH relative to 10 6 The main chain has fewer than 100 carbon atoms.
7. An injection-molded article comprising any one of claims 1 to 6.
8. A coated wire having a coating layer comprising a fluorinated copolymer according to any one of claims 1 to 6.
9. A molded article comprising the fluorinated copolymer according to any one of claims 1 to 6, wherein, The molded body is a bolt, filter cover, tube, membrane, or wire cover.
Citation Information
Patent Citations
Tetrafluoroethylene / hexafluoropropylene copolymer and the production method thereof, and electrical wire
WO2009102660A1
Semi-persistent scheduling resource allocation method and base station
WO2016050166A1
Layered body and tube
WO2019220850A1
Tetrafluoroethylene terpolymers
US4029868A
Resin composition
WO2019225694A1